Prepare, succeed, advance : a guidebook for getting a PhD in biblical studies and beyond - Gupta, Nijay K. (Lutterworth Press, 2017)
An informative and valuable guide to the process of obtaining a doctorate in Biblical Studies and the subsequent steps towards an academic career.